Riboflavin Status in Pregnancy and Its Relationship with Blood Pressure, Heart Rate and Risk of Hypertension: Findings from the OptiPREG Observational Study - Bethany Duffy; Helene McNulty; Mary Ward; Elina Psara; Emma O’Sullivan; Geraldine Horigan; Kristina Pentieva (Proceedings)
Clinical riboflavin deficiency is common in low- and middle-income countries, whilst sub-optimal riboflavin status may be much more prevalent globally than generally recognized, including in high-income countries. Riboflavin biomarkers are rarely assessed in humans, with most studies reliant on dietary intakes only, therefore the health consequences of riboflavin deficiency remain largely uninvestigated. Our previous trials in non-pregnant adults demonstrated that supplemental riboflavin can significantly lower blood pressure (BP), specifically among individuals homozygous (TT genotype) for the common MTHFR C677T polymorphism. Little is known about the role of riboflavin in BP during pregnancy. The aim of this study was to examine the association of riboflavin status with BP, heart rate and risk of hypertension in pregnancy (HIP) at the 12th gestational week. Observational data from healthy Irish pregnant women enrolled in the OptiPREG study were analysed (n = 2236). Riboflavin status was determined using the functional assay erythrocyte glutathione reductase activation coefficient (EGRac), whereby higher values indicate lower riboflavin status. We identified a deficient riboflavin status (EGRac ≥ 1.40) in 31% of participants, despite riboflavin supplement usage reported by the majority (64%). EGRac was a significant determinant of systolic (β = 3.390, p = 0.011) and diastolic (β = 2.875, p = 0.003) BP, following adjustment for gestational age, maternal age, BMI, parity, smoking and MTHFR genotype. Riboflavin deficiency was associated with an almost three-fold greater risk of developing HIP (OR = 2.906, p = 0.041). Within quartiles of riboflavin status, ranging from best (Q1) to poorest status (Q4), there were stepwise increases in heart rate (mean ± SD, bpm; 79.9 ± 10.5 (Q1); 81.1 ± 9.7 (Q2); 81.8 ± 10.9 (Q3); 83.3 ± 11.3 (Q4), p = 0.037), following adjustment for gestational age, maternal age and BMI. The prevalence of HIP increased as riboflavin status deteriorated, with the highest prevalence observed among those with the poorest riboflavin status (4.3% (Q1); 4.9% (Q2); 6.6% (Q3); 8.0% (Q4), p = 0.039). The maintenance of an optimal riboflavin status in pregnancy, through improved diet, fortification and/or supplementation, may improve BP and heart rate, and reduce the risk of HIP. The observational findings presented here require confirmation in randomised trials with riboflavin in pregnancy, including the ongoing OptiPREG RCT.